Evaluación de tres niveles de harina de Alfalfa (Medicago Sativa) al 5%, 10% y 15% en la alimentación en pollos de engorde - Vargas Herrera, Angie Nicole (2023)
This research objective was to evaluate the inclusion of three levels of alfalfa meal (HA) at 5, 10 and 15 % compared to a conventional balanced control treatment in the broiler chicken’s diet. The chickens were raised in the Pichincha province, Quito Metropolitan District (DMQ), Eloy Alfaro parish, at an altitude of 2860 msnm. 100 poultry, broiler cobb 500 genetic lineage, with 10 days of age, were distributed in four treatments T0 (0% HA), T1 (5% HA), T2 (10% HA) and T3 (15% HA), each with 4 replicates of 25 birds, to evaluate the effects of alfalfa meal on weight gain, feed intake, feed conversion, carcass yield, skin pigmentation and cost-benefit, at day 52. When determining the body weights in each of the treatments, was found that on day 52, the control treatment obtained the best results with a final weight of 3031.8 grams, with statistically significant differences (P<0.05), carcass weight of 2600 grams and final yield of 75.95%. In addition, the treatment with 5% inclusion, obtained acceptable results, being the second option compared to the final weights obtained with 2956.1 grams. Feed conversion had a high percentage on day 52, in all treatments, with an interval of 2.06% to 2.24%, the cause of the ascitic syndrome incidence is presumed. When evaluating the pigmentation, the T3 treatment showed adequate results with a yellow coloration in the carcass. In the same way, the positive cost benefit generated during the research development, was registered in the control treatment with a net benefit of 0.23 USD. The fiber percentage implemented influenced the productive parameters of the birds.